KEKAYAAN BEGONIA TAMAN NASIONAL GUNUNG HALIMUN - Harry Wiriadinata; Deden Girmansyah; Scott Hoover; James Hunter (BERITA BIOLOGI, 2002)
Begonias arc unique due to asymmetric leaves, and they have large variation on their coloration and hairiness. The flower is unisexual, male and female flowers are in separate branches.The fruit with or without wings of different size and shape.Those unique characters attract them as ornamental plants, Mts. Halimun National Park has many species of wild Begonias which can be found on the forest floor.They grow in group and have essential role in mountainous forest ecosystem. Exploration for wild Begonia within forest around Cikaniki,Cirnarasa. Koridor Cianten, Gn, Botol, Gn. Bintang Gading, Gn. Sanggabuana will be presented in this paper.